2016
DOI: 10.1503/cmaj.150858
|View full text |Cite
|
Sign up to set email alerts
|

A population-based analysis of incentive payments to primary care physicians for the care of patients with complex disease

Abstract: See also www.cmaj.ca/lookup

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 28 publications
3
35
0
Order By: Relevance
“…1 In Canada, some provinces have implemented pay-for-performance incentives, particularly for primary care phys icians, [2][3][4][5][6] despite the equivocal and limited nature of the evidence supporting them. In September 2011, the government of Ontario introduced bonus payments to encourage psychiatrists to provide rapid access to patients within 30 days of discharge after a psychiatric hospital admission and for 6 months after a suicide attempt.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 In Canada, some provinces have implemented pay-for-performance incentives, particularly for primary care phys icians, [2][3][4][5][6] despite the equivocal and limited nature of the evidence supporting them. In September 2011, the government of Ontario introduced bonus payments to encourage psychiatrists to provide rapid access to patients within 30 days of discharge after a psychiatric hospital admission and for 6 months after a suicide attempt.…”
mentioning
confidence: 99%
“…In British Columbia, incentives have been implemented to encourage primary care phys icians to create mental health care plans in collaboration with patients with a diagnosed mental illness. 4 In this study, we investigated whether psychiatrists changed their practice patterns in response to the September 2011 incentives, and whether patients at high risk had better access to psych iatrists. Our research questions were as follows: What is the effect of financial incentives on psychiatrist supply of community-based mental health and addiction care after discharge from hospital or after a suicide attempt?…”
mentioning
confidence: 99%
“…Incentives were implemented for a wide range of primarily chronic conditions. 1,2 The article by Lavergne and colleagues, entitled "A population-based analysis of incentive payments to primary care physicians for the care of patients with complex disease", 3 provides only a partial picture of the program by neglecting to provide important context. It confuses one incentive payment (the Complex Care Maintenance Fee) with the broad FSFPIP (calling the single fee the "Complex Care Initiative"), and erroneously suggests the whole program was ineffective.…”
mentioning
confidence: 99%
“…"Patients and their caregivers must be involved in decision-making at all steps in the research process, from design to choice of primary and secondary outcomes …" As an example of failure to do this, she cites a study 2 that found that incentive payments to primary care physicians for providing care to patients with multiple chronic conditions did not have a significant impact on patients' primary care contacts, continuity of care or management costs. Patrick criticizes the paper for the fact that "the outcomes were almost certainly not patient-relevant."…”
mentioning
confidence: 99%